PENGARUH GRAVIDA, PEKERJAAN, DUKUNGAN SUAMI, DUKUNGAN BIDAN/TENAGA KESEHATAN TERHADAP PARTISIPASI IBU DALAM KELAS IBU HAMIL DI KABUPATEN MAGELANG - Masini Masini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2015)
Class of pregnant women is a means to learn together about the health of pregnant women in the form of face-to-face in a group that aims to improve the knowledge, skills regarding pregnancy, childbirth, postpartum care, newborn care, infectious disease.In Magelang District in 2012 there were 3760 women who participated (16.4%) in the class of 22 946 pregnant women pregnant women. In 2013 women who participated in the class of 9398 pregnant women (43%) of 21 811 pregnant women.The purpose of research to determine the effect gravida, job, husband support, support midwife / health workers against the mother's participation in the class of pregnant women in Magelang District.The form of an explanatory research with cross sectional approach. The population in this study are all mo-thers who have given birth in the last 6 months Magelang district health center. Sampling with formula Slovin and simple random sampling technique of the 100 pregnant women. Bivariate chi-square test and multivariate logistic regression.The results showed that participating mothers are less active and each has a percentage of 50%. While the factors that are not related to participation in class is gravida pregnant women, work, support midwife / health workers. Factors that have a relationship with the participation of pregnant women in the class that support the husband.Factors that influence the participation of pregnant women in the class is the husband support.